MP2P high capacity and security resource node selection strategy based on Bayesian game - Yan LIU; yin ZHANGGuo; zhou HEJin; Feng XU (Tongxin xuebao)
Considering the changes of MP2P topology due to the limitation of the capability, the unreliable and the churn of the node, the efficiency and safety resource node selection strategy based on Bayesian game were proposed in MP2P network. Firstly, the safety resource calculation method was designed that takes the node capability and the node reputa-tion into consideration. Secondly, adopting the Bayesian game theory to connect the resource nodes, ensuring the re-questing node can intercommunicate with the high efficiency and safety resource node, the strategy can efficiently reduce failure rate of the resource nodes, greatly improving the network efficiency.